Friction electric whisker sensor based on liquid metal - GUO ZINAN; LIU BO; LEE WON-JEONG; WANG TIANRUN; XU PENG; LIU JIANHUA; XU MINYI; GUAN TANGZHEN; GUO LINAN (2024)
A triboelectric whisker sensor based on liquid metal is characterized in that carbon fiber material whiskers sense a measurement environment, a trigger is swung to press four fan-shaped sensing units, the four fan-shaped sensing units return to the original position through memory alloy springs, and when an external load acts, silica gel and hydrogel on the upper portion bend and move downwards, so that the measurement environment is measured. Potential balance between the silica gel and the liquid metal at the bottom is broken, current flows to the liquid metal electrode from the hydrogel electrode slice, charge transfer is finished after the liquid metal layer is tightly attached to the upper silica gel, and outward elastic force generated in the silica gel drives the silica gel to recover to the initial shape after external load disappears. After the silica gel and the liquid metal are separated, potential balance on the surfaces of the silica gel and the liquid metal is broken again to form potential diff